Post-Socialist Financial Fragility: the Case of Albania - Dirk J. Bezemer (Tinbergen Institute, 1999)
The 1997 collapse of the Albanian economy caused by the collapse of economy-widePonzi schemes contrasts sharply to itssuccess status as a post-socialist transition country in the years 1992-1996. Inthis paper, an attempt is made to explain this'Albanian Paradox'. The specific Albanian conditions for the growth of Ponzischemes are identified. Theoretically, theAlbanian Paradox can be interpreted as one version of the 'Financial InstabilityHypothesis' suggested by Minsky.Investigation of the underlying factors that render financial markets fragilesuggests that the Albanian case is extreme butnot rare in the region. In the post-socialist setting, expectations of thepopulation and other potential investors based on alack of reliable information on returns may lead to excessive capital inflow.This trend is reinforced if governments areweak, and if transition policies rely largely on liberal financial marketdevelopment, rapid privatisation and external capitalinflows, facilitating the tendency to instability. Identification of this trendis hindered if policy makers and observers largelyrely on macroeconomic indicators in monitoring the economy.
Keywords: E12; G18; O5; P27; P34; 330; Systemtransformation; Albanien; Finanzkrise